THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON THE DECISION TO PURCHASE LG TV AT SIKAPAIYA SHOP, MAJENE DISTRICT - Hartawati, Sri Indira (Jurnal Ekonomi Balance, 2019)
This study aims to find out how the effect of Product Quality on LG TV Purchase Decisions at the Sikapaiya Shop in Majene Regency, how the effect of Price on LG TV Purchase Decisions at Sikapaiya Shop in Majene Regency and which variables are more dominant influence on LG TV Purchase Decisions at Sikapaiya Shop Majene Regency. The type of research used is quantitative and qualitative with data collection techniques using library studies, observation, interviews and documentation. The data analysis technique used in this study is qualitative data analysis, the concept of qualitative data analysis is an activity that includes validation test data, reliability test, partial test (t test). The results showed that 1) Product Quality had a significant effect on LG TV Purchase Decisions at Sikapaiya Shop in Majene Regency. 2) Price has no significant effect on LG TV Purchase Decisions at Sikapaiya Shop, Majene Regency. 3) Product Quality has more significant effect on LG TV Purchase Decisions at Sikapaiya Shop in Majene Regency.